Long-run effects of fiscal policies on environmental pollution - Derya Tabiloğlu; Temel Gürdal (Entrepreneurial Business and Economics Review (EBER), 2025)
Objective: This study aims to investigate the long-run effects of fiscal policy instruments, including environmental taxes, environmental protection expenditures and renewable energy incentives on environmental pollution, measured as ecological footprint, in a sample of European Union countries and Turkey using annual data for the period 1996-2018. Research Design & Methods: The conventional literature generally suggests that fiscal policy instruments can affect environmental pollution in the long run. To examine whether fiscal policy instruments will be effective on pollution in the long run, we employed both fully modified ordinary least squares (FMOLS) and dynamic ordinary least squares (DOLS) methods. Findings: The estimation results showed that renewable energy incentives are the most effective policy instrument to mitigate pollution. We also found that environmental taxes have negative and statistically significant effects on pollution. However, the relationship between environmental protection expenditures and pollution is not robust and changes with respect to the estimation method. Implications & Recommendations: The findings of this study indicate that fiscal policy instruments can reduce environmental pollution. In this vein, renewable energy incentives and environmental tax tools appear to be the most effective fiscal policy instruments. Therefore, policymakers can use fiscal policy instruments to deal with environmental pollution problems. Contribution & Value Added: Given the limited research on the combined effects of fiscal policy instruments, we aimed to contribute to the literature by employing FMOLS and DOLS estimation procedures. These methods allowed us to examine the long-run relationship between fiscal policy instruments and the ecological footprint. To examine the long-run relationship between fiscal policy instruments and ecological footprint, we prefer to employ FMOLS and DOLS methods which consider potential autocorrelation and some degree of heterogeneity. Therefore, we aimed to contribute to the literature by investigating the effectiveness of fiscal policy instruments on environmental pollution in our sample of countries.
Keywords: E62; H23; Q28; 330; environmental pollution; environmental protection expenditures; environmental taxes; fiscal policies; renewable energy resources